Classical scattering of an ion influenced by polarization effect of dust particles - Ramazanov, T.S.; Kodanova, S.K.; Bastykova, N.Kh.; Moldabekov, Zh.A.; Agatayeva, A.A. (Recent Contributions to Physics, 2018)
In this paper, the classical processes of scattering and absorption of ions by a dust particle was investigated. Corrections to the classical ion-grain scattering and capture cross sections due to polarization charges on the dust particle, which acts as an image charge, have been obtained for a low charged grain (with the charge number Z = 10). The trajectory of the ion around the dust particle is used for visual illustration of the influence of the grain polarization on scattering. The correction to the scattering cross section due to the image force can be as large as 25 % in the strong ion-grain coupling regime and up to 10 % in the moderately coupled case. The correction to the capture cross section turns out to be nearly constant (14 %) for moderate as well as strong ion-grain coupling. In studies of gases with low density and degree of ionization, or in the presence of relatively weak radiation in interstellar space, it is important to know the dynamics of a dust particle with a low charge.